Intrathecal tocilizumab for immune-mediated central nervous system complication after haploidentical hematopoietic stem cell transplantation in children: Two case reports - Ruirui Gui; Zhen Li; Juan Wang; Yingling Zu; Binglei Zhang; Juanjuan Zhao; Yongping Song; Jian Zhou (Heliyon)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an effective measure for the treatment of hematological disease. With the progress and wide use of allo-HSCT, post-transplant central nervous system complications (CNSC) have gotten more and more attention because of its poor prognosis and high mortality. Since there is no standard treatment for patients with immune-mediated CNSC currently, new treatments are needed to be developed urgently. Here, we attempted a novel therapy regimen of intrathecal tocilizumab injection in two pediatric patients with immune-mediated CNSC manifested as cytokine release syndrome (CRS) after haploidentical hematopoietic stem cell transplantation (halpo-HSCT). In the two patients, persistent seizure symptoms could not be resolved 7 h after intravenous tocilizumab, while the symptoms were controlled rapidly only 2 hours or 1 hour after the first intrathecal injection of tocilizumab. Moreover, the level of interleukin 6 in the cerebrospinal fluid returned to normal after the fifth intrathecal injection. Even more appealing, no acute or chronic adverse reactions were observed during injection and subsequent follow-up. In conclusion, intrathecal tocilizumab seems to be more rapid and effective than intravenous administration for immune-mediated CNSC manifested as CRS in haplo-HSCT recipients. We recommend this treatment modality for further investigation.